2020
DOI: 10.34172/jlms.2020.70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Irradiance and Fluoride Varnish on Demineralization Around Dental Composite Restorations

Abstract: Introduction: This study aimed to assess the effects of CO2 and erbium-doped yttrium aluminum garnet (Er:YAG) lasers with and without fluoride varnish on demineralization around composite restorations. Methods: This in vitro experimental study evaluated 96 extracted human premolars. After preparation and restoration of class V cavities in the buccal surface of the teeth with composite resin, they were randomly divided into 8 groups of control, CO2 laser (L1), CO2 laser-NaF (L1F), NaF-CO2 laser (FL1), Er:YAG la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Remin Pro contains HFX and can fill superficial enamel defects [ 30 , 31 ]. In this regard, Valizadeh et al [ 32 ] concluded that application of Er:YAG and CO 2 lasers alone could not significantly improve the resistance of dental tissues to caries; nevertheless, they had synergistic effects together with sodium fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…Remin Pro contains HFX and can fill superficial enamel defects [ 30 , 31 ]. In this regard, Valizadeh et al [ 32 ] concluded that application of Er:YAG and CO 2 lasers alone could not significantly improve the resistance of dental tissues to caries; nevertheless, they had synergistic effects together with sodium fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…There is still a debate regarding the use of Er:YAG laser irradiation before or after fluoride coating. To achieve better results in enhancing tooth structural resistance and enamel hardness, Valizadeh et al [ 31 ] proposed the application of fluoride varnish or gel before laser irradiation. Er:YAG laser irradiation after the application of fluoride has the potential to melt and seal the dentin tubules, thereby preventing the fluoride from going further into the dentine.…”
Section: Discussionmentioning
confidence: 99%
“…There are significant studies in the literature about the effects of laser usage in the fluorination protocols before and after fluoride treatment, evidencing improved fluoride absorption and enamel re-mineralization stimulation [ 6 , 7 , 8 , 9 ]. The active compounds within Tiefenfluorid are sodium fluoride and dispersed calcium hydroxide, which are involved in the newly formed fluoride crystals [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%